Proximal tubular deletion of superoxide dismutase-2 reveals disparate effects on kidney function in diabetes - Inez A. Trambas; Lilliana Bowen; Vicki Thallas-Bonke; Matthew Snelson; Karly C. Sourris; Adrienne Laskowski; Michel Tauc; Isabelle Rubera; Guoping Zheng; David C.H. Harris; Phillip Kantharidis; Takahiko Shimizu; et al. (Redox Biology)
There is a large body of evidence implicating mitochondrial reactive oxygen species (ROS) overproduction and oxidative stress in the development of diabetic kidney disease and the deficiency of mitochondrial antioxidant systems in the kidney, such as manganese superoxide dismutase (MnSOD/SOD2) have been identified. The proximal tubules of the kidney are densely packed with mitochondria thereby providing energy via oxidative phosphorylation in order to drive active transport for proximal tubular reabsorption of solutes from the glomerular filtrate. We hypothesized that maintenance of MnSOD function in the proximal tubules would be critical to maintain kidney health in diabetes. Here, we induced targeted deletion of SOD2 in the proximal tubules of the kidney in Ins2Akita diabetic mice (SODptKO mice) and show that 20 weeks of SOD2 deletion leads to no major impairment of kidney function and structure, despite these mice displaying enhanced albuminuria and kidney lipid peroxidation (8-isoprostanes). Plasma cystatin C, which is a surrogate marker of glomerular filtration was not altered in SODptKO diabetic mice and histological assessment of the kidney cortex revealed no change in kidney fibrosis. Thus, our findings suggest that deletion of SOD2 in the proximal tubular compartment of the kidney induces a more subtle phenotype than expected, shedding light on the involvement of SOD2 and the proximal tubular compartment in the pathogenesis of diabetic kidney disease.